Adult abdominal Burkitt lymphoma with isolated peritoneal involvement - Oliveira, C (2014)
Burkitt lymphoma is a fast-growing high grade B-cell neoplasm that rarely affects adults. Three clinical variants are described in the World Health Organization classification: endemic, sporadic, and immunodeficiency-associated. The non-endemic form typically presents as an abdominal mass in children. Symptoms usually occur due to mass effect or direct intestinal involvement. We describe a very unusual presentation of a sporadic Burkitt lymphoma case in a 61-year-old male with diffuse peritoneal and omental involvement, without lymphadenopathies, mimicking peritoneal carcinomatosis.